Determinants of Maternal Mortality Rate in Grobogan (Universitas Negeri Semarang, 2022)
The maternal mortality rate is a reflective indicator of mother health statuses. The impact of the high maternal mortality rate also describes the poor degree of community health. This situation potentially degrades the economic growth and social levels at domestic, community, and national levels. This research analyzed the influential determinant of maternal mortality rate in Grobogan Regency. This quantitative research used an applied controlled-case study. The sample consisted of 36 cases with 36 and 72 controlled cases within a 1:2 ratio. The researcher used the total sampling technique to take the sample of the case group. On the other hand, the researchers simple random sampling technique to take the controlled-group sample. The independent variables were high-risk pregnancy, health care service access, and antenatal care with complications as the intervening variables; and maternal mortality as the dependent variable. The researchers used bivariate analysis with Chi-Square and multivariate analysis with the path analysis. The results showed the influences between high-risk pregnancy, antenatal care, and complication on maternal mortality rate. The researchers also found high-risk pregnancy influenced maternal mortality via complications.